3D Computed Tomography Reconstruction for Pre‐Operative Diagnosis of Anomalous Venous Drainage of the Right Upper Lobe - Maria Antonietta Puca; Antonio Marella; Maria Marvulli; Anna Rainone; Francesca Capasso; Vincenzo diFilippo; Gaetana Messina; Alfonso Fiorelli (Thoracic Cancer)
ABSTRACT Anatomical variation of the pulmonary vessels poses challenges to thoracoscopic lung resection and may be associated with an increased risk of intraoperative bleeding and damage to pulmonary circulation. Herein, we reported a rare and dangerous variation as the partial anomalous venous drainage of the right upper lobe into the superior vena cava in a patient undergoing thoracoscopic lobectomy for management of lung cancer of right upper lobe. The preoperative identification of such variation by 3D computed tomography scan allowed to plan a safe and accurate resection, and to prepare additional strategies for overcome unexpected intraoperative bleeding. No intraoperative and/or postoperative complications were observed. Chest drainage was removed on postoperative day two and patient discharged the day after. At 3 months follow up, the patient was well without recurrence.